An electric stove with four burners and an oven is used in preparing a meal as follows. Burner 1: 20 minutes Burner 2: 40 minutes Burner 3:

Question

An electric stove with four burners and an oven is used in preparing a meal as follows. Burner 1: 20 minutes Burner 2: 40 minutes Burner 3: 15 minutes Burner 4: 45 minutes Oven: 30 minutes If each burner is rated at 1.1 kW and the oven at 2.5 kW, and electricity costs 12 cents per kWh, calculate the cost of electricity used in preparing the meal. slader

in progress 0
Đan Thu 1 week 2021-07-21T18:59:55+00:00 1 Answers 3 views 0

Answers ( )

    0
    2021-07-21T19:00:59+00:00

    Answer:

    41.4 cents

    Explanation:

    The Quantity of heat used  up is expressed as H = Power * Time

    For Burner 1;

    Power rating= 1.1kW

    Time used = 20mins = (20/60)hr

    Time (in hour) = 1/3 hr

    H = 1.1* 1/3

    H = 11/10*1/3

    H = 11/30kWh

    For Burner 2;

    Power rating= 1.1kW

    Time used = 40mins = (40/60)hr

    Time (in hour) = 2/3 hr

    H = 1.1* 2/3

    H = 11/10*2/3

    H = 22/30kWh

    H = 11/15 kWh

    For Burner 3;

    Power rating= 1.1kW

    Time used = 15mins = (15/60)hr

    Time (in hour) = 1/4 hr

    H = 1.1* 1/4

    H = 11/10*1/4

    H = 11/40kWh

    For Burner 4;

    Power rating= 1.1kW

    Time used = 45mins = (45/60)hr

    Time (in hour) = 3/4 hr

    H = 1.1* 3/4

    H = 11/10*3/4

    H = 33/40kWh

    For Oven;

    Power rating= 2.5kW

    Time used = 30mins = (30/60)hr

    Time (in hour) = 1/2 hr

    H = 2.5* 1/2

    H = 25/10*1/2

    H = 25/20kWh

    H = 5/4 kWh

    Total Quantity of energy used = 11/30+11/15+11/40+33/40+5/4

    Total Quantity of energy used = (44+88+33+99+150)/120

    Total Quantity of energy used = 414/120

    Total Quantity of energy used = 3.45kWh

    If 1kWh costs 12 cents

    3.34kWh will costs (12*3.45)cents

    3.34kWh will cost 41.4cents

    Hence the cost of electricity used in preparing the meal is 41.4 cents

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )